Coated modified positive electrode material, preparation method thereof and lithium battery
Patent Information
- Application Number
- CN202611270402.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-20
- Publication Date
- 2026-10-16
AI Technical Summary
固相包覆工艺简单、易于工业化量产,但包覆均匀性差,易形成岛状非连续包覆层,导致材料本体裸露并与电解液发生副反应,劣化电化学与安全性能,且通常需要较高的烧结温度;行业内也有采用纳米微晶氧化物低温包覆的路线,但纳米微晶物质本征易团聚,易出现局部堆积、颗粒凹陷处包覆不足的问题,材料表面仍存在电解液可渗透的裸露位点,难以实现电化学性能的有效提升;液相包覆可实现相对均匀的包覆效果,但存在废液污染、工艺成本偏高的问题;气相包覆可实现原子级均匀包覆,但设备与运维成本很高,难以满足工业化大规模生产需求
本发明通过熔融淬火法对正极材料进行包覆改性,该方法以助熔剂为熔融介质,通过分段控温,先在较低温度下使助熔剂熔融形成均匀的液相介质,包覆源在液相介质中均匀分散,液相介质充分浸润正极材料表面并带动包覆源均匀附着于正极材料基体表面;再在较高温度下使已附着的包覆源原位形成均匀、致密、与基体结合良好的包覆层,结合快速淬火锁定包覆层的结晶状态,避免晶粒长大对包覆层均匀性造成破坏;本发明方法能避免传统固相法易形成的岛状、点状非连续包覆,有效隔绝电解液侵蚀,抑制界面副反应及过渡金属溶解;同时无废液污染,设备成本低。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery technology, and more specifically, to a coated modified cathode material, its preparation method, and a lithium battery. Background Technology
[0002] With the widespread application of lithium-ion batteries in new energy vehicles, energy storage, and consumer electronics, the market has placed higher demands on their energy density, cycle life, and safety performance. As one of the determining factors of battery performance, the performance optimization of cathode materials is the core of technological development. Increasing the operating voltage or specific capacity of the material can effectively improve the overall energy density of the battery, but this often comes with a decrease in the stability of the material interface. Under high-voltage cycling conditions, side reactions between the electrode material and the electrolyte intensify, leading to problems such as transition metal dissolution and structural degradation, severely degrading the electrochemical performance and safety of the battery.
[0003] Surface coating is a core technology for improving the interfacial stability of cathode materials. Existing coating technologies are mainly divided into three categories: solid-phase coating, liquid-phase coating, and gas-phase coating. Solid-phase coating is simple and easy to mass-produce industrially, but it suffers from poor coating uniformity and is prone to forming island-like discontinuous coating layers, leading to the exposure of the material body and side reactions with the electrolyte, deteriorating electrochemical and safety performance. It also usually requires high sintering temperatures. There is also a route in the industry that uses low-temperature coating with nanocrystalline oxides, but nanocrystalline materials are inherently prone to agglomeration, resulting in local accumulation and insufficient coating at particle depressions. There are still exposed sites on the material surface that can be penetrated by the electrolyte, making it difficult to effectively improve electrochemical performance. Liquid-phase coating can achieve a relatively uniform coating effect, but it has problems such as waste liquid pollution and high process costs. Gas-phase coating can achieve atomic-level uniform coating, but the equipment and maintenance costs are very high, making it difficult to meet the needs of large-scale industrial production.
[0004] Therefore, developing a novel coating technology that can balance coating uniformity and process economy to overcome at least one of the above-mentioned defects in existing coating technologies, thereby effectively improving the electrochemical performance of cathode materials, has significant research significance and industrial application value.
[0005] In view of this, the present invention is hereby proposed. Summary of the Invention
[0006] The purpose of this invention is to provide a coated modified cathode material, its preparation method, and a lithium battery. The method uses a flux as a melting medium and achieves full wetting and uniform adhesion of the coating source to the surface of the cathode material substrate through staged temperature control, forming a coating layer that is well bonded to the substrate. Subsequently, the crystallization state of the coating layer is locked by rapid quenching to prevent grain growth, thereby obtaining a modified cathode material with a continuous and dense coating layer, which effectively isolates electrolyte erosion and inhibits interfacial side reactions and transition metal dissolution.
[0007] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: A method for preparing a coated and modified cathode material includes the following steps: S1. The positive electrode material matrix is mixed with the coating source and flux to obtain a mixture; S2. The mixture is subjected to segmented heat treatment in an oxygen-containing atmosphere, the segmented heat treatment comprising: heating the mixture to a first temperature and holding it at that temperature, then continuing to heat it to a second temperature and holding it at that temperature, wherein the first temperature is higher than the melting point of the flux, and the second temperature is greater than the first temperature; S3. After the segmented heat treatment is completed, cooling is performed at a rate of ≥20℃ / min.
[0008] Preferably, the first temperature is 300~500℃, and the heat preservation time at the first temperature is 1~4h.
[0009] Preferably, the second temperature is 650~850℃, and the holding time at the second temperature is 2~6h.
[0010] Preferably, the chemical formula of the positive electrode material matrix is Li. a Ni x Co y Mn z In the chemical formula O2, 0.97≤a≤1.10, 0≤x≤1.0, 0≤y≤1.0, 0≤z≤1.0, and x+y+z=1.
[0011] Preferably, the coating source includes at least one of a compound containing M, boric acid, and phosphoric acid, wherein M is selected from at least one of Al, Zr, Mg, Ti, Li, Y, La, Co, Zn, Ce, Si, Ge, Sc, Ga, Ta, and Nb; the compound containing M includes at least one of oxides, hydroxides, alkoxides, acetates, borates, phosphates, hydrogen phosphates, dihydrogen phosphates, pyrophosphates, carbonates, and oxalates containing M.
[0012] Preferably, the flux includes at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium fluoride, lithium phosphate, lithium metaborate, and lithium metaphosphate.
[0013] Preferably, the amount of the coating source added accounts for 0.1% to 5% of the mass of the cathode material matrix.
[0014] Preferably, the amount of flux added accounts for 0.2% to 3% of the mass of the positive electrode material matrix.
[0015] A coated modified cathode material is prepared by any one of the preparation methods described in the preceding embodiments; the coated modified cathode material includes a cathode material matrix and a coating layer covering the surface of the cathode material matrix.
[0016] Preferably, the coating layer comprises a metal oxide and / or a lithium-based fast ion conductor.
[0017] Preferably, the lithium-based fast ion conductor includes at least one of the following: NASICON type oxide fast ion conductor, garnet type oxide fast ion conductor, glassy composite lithium fast ion conductor, Li3PO4 fast ion conductor, LiBO2 fast ion conductor, LiAlO2 fast ion conductor, and LiNbO3 fast ion conductor.
[0018] A lithium battery comprising the coated modified cathode material described in any of the foregoing embodiments.
[0019] Compared with the prior art, the beneficial effects of the present invention are as follows: This invention modifies cathode materials through a melt-quenching method. Using a flux as the melting medium, and through segmented temperature control, the flux is first melted at a lower temperature to form a uniform liquid medium. The coating source is uniformly dispersed in this liquid medium, which fully wets the surface of the cathode material and causes the coating source to adhere uniformly to the substrate surface. Then, at a higher temperature, the adhered coating source forms a uniform, dense coating layer in situ, well-bonded with the substrate. Rapid quenching locks in the crystallization state of the coating layer, preventing grain growth from damaging its uniformity. This method avoids the island-like and dot-like discontinuous coatings easily formed by traditional solid-state methods, effectively isolates electrolyte erosion, and suppresses interfacial side reactions and transition metal dissolution. Furthermore, it produces no waste liquid pollution and has low equipment costs.
[0020] The coating method of the present invention is compatible with traditional oxide coating and lithium fast ion conductor coating, and can take into account both physical protection and ion conduction functions. It can stabilize the surface structure of the material, reduce the generation of microcracks during cycling, accelerate lithium ion transport, and reduce interface impedance, thereby simultaneously improving the specific capacity, cycle stability and thermal safety performance of the cathode material. Detailed Implementation
[0021] The technical solution of the present invention will be clearly and completely described below with reference to specific embodiments. However, those skilled in the art will understand that the embodiments described below are some embodiments of the present invention, but not all embodiments, and are only used to illustrate the present invention, and should not be regarded as limiting the scope of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention. Where specific conditions are not specified in the embodiments, conventional conditions or conditions recommended by the manufacturer shall be followed. Where the manufacturers of reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0022] The first aspect of the present invention provides a method for preparing a coated modified cathode material, comprising the following steps: S1. The positive electrode material matrix is mixed with the coating source and flux to obtain a mixture; S2. The mixture is subjected to segmented heat treatment in an oxygen-containing atmosphere. The segmented heat treatment includes: heating the mixture to a first temperature and holding it at that temperature, then heating it to a second temperature and holding it at that temperature. The first temperature is higher than the melting point of the flux, and the second temperature is higher than the first temperature. S3. After the segmented heat treatment is completed, the cooling rate is ≥20℃ / min; for example, the cooling rate can be any one value or a range of any two values among 20℃ / min, 25℃ / min, 30℃ / min, 35℃ / min, 40℃ / min, 50℃ / min, and 80℃ / min.
[0023] This invention employs a melt-quenching method to modify cathode materials through coating. First, a low-temperature pre-melting treatment completely melts the flux to form a homogeneous liquid phase medium. Then, a high-temperature coating treatment achieves nanoscale pre-spreading of the coating source. Finally, rapid quenching and cooling to room temperature locks in the uniform nanocrystalline structure of the coating phase, resulting in a cathode active material product with a uniformly coated nanocrystalline surface. This method is applicable to the coating modification of all cathode materials, especially ternary cathode materials.
[0024] This invention achieves uniform coating of the cathode material surface through the synergistic combination of a molten medium environment, segmented temperature-controlled coating, and rapid cooling. Specifically: (1) Molten medium environment: When heated to above the melting point of the flux, the flux melts to form a liquid medium. This liquid medium wets the surface of the cathode material matrix, so that the coating source spreads evenly on the matrix surface with the liquid phase, avoiding local agglomeration of the coating source. On the other hand, the liquid mass transfer reduces the reaction activation energy of the coating source, so that the coating reaction can be carried out at a relatively low temperature.
[0025] (2) Segmented temperature control: The present invention divides the heating process into two stages. The first stage is low temperature holding, which allows the flux to completely melt and form a stable liquid medium. The flux forms a flow layer, which drives the coating source to flow on the substrate surface, so that the coating source can fully diffuse, wet and uniformly adhere to the surface of the positive electrode material in the liquid phase, thus achieving the full completion of the "attachment" process. The second stage is held at a higher temperature, which aims to make the attached coating source form a uniform, dense coating layer with good adhesion to the substrate in situ. If the coating source is the precursor of the final coating material, it will undergo a decomposition and nucleation reaction in the second stage. The coating source will decompose in the flux environment to generate fine nanocrystalline particles that are firmly attached to the substrate surface. If the coating source is the final coating material itself, the second stage will make the coating layer more tightly bonded to the substrate.
[0026] If only the first-stage low-temperature insulation process is carried out, the coating source precursor may not undergo a decomposition reaction and a stable coating layer cannot be formed; if only the second-stage high-temperature insulation process is carried out, the coating source is not fully wetted by the flux, and the resulting coating layer will be uneven, easily forming island-like or dot-like coatings.
[0027] (3) Rapid cooling: After the heat preservation is completed, the material is rapidly cooled down by rapid cooling. The strong supercooling prevents the grains from growing, thereby locking the uniform crystallization state of the coating layer and obtaining a modified cathode material with a uniform and dense coating layer.
[0028] In this invention, the molten medium environment provides a liquid-phase basis for the uniform dispersion and adhesion of the coating source; segmented temperature control ensures the uniformity and structural integrity of the coating layer during its formation; and rapid cooling locks in the already formed uniform crystalline state, preventing subsequent grain growth from damaging the uniformity. These three factors work synergistically to achieve a uniform, dense coating layer with good adhesion to the matrix, effectively stabilizing the surface structure of the cathode material, reducing microcrack formation during cycling, and improving the electrochemical performance of the material.
[0029] In some specific embodiments of the present invention, the first temperature is 300~500℃, for example, it can be any one value or a range of any two values among 300℃, 350℃, 400℃, 450℃, and 500℃; the heat preservation time at the first temperature is 1~4h, for example, it can be any one value or a range of any two values among 1h, 2h, 3h, and 4h.
[0030] In some specific embodiments of the present invention, the second temperature is 650~850℃, for example, it can be any one value or a range of any two values among 650℃, 700℃, 750℃, 800℃, and 850℃; the heat preservation time at the second temperature is 2~6h, for example, it can be any one value or a range of any two values among 2h, 3h, 4h, 5h, and 6h.
[0031] In some specific embodiments of the present invention, the general chemical formula of the cathode material matrix is Li. a Ni x Co y Mn z In the chemical formula O2, 0.97≤a≤1.10, 0≤x≤1.0, 0≤y≤1.0, 0≤z≤1.0, and x+y+z=1.
[0032] In some specific embodiments of the present invention, the method for preparing the positive electrode material matrix includes the following steps: The precursor is mixed with lithium salt and sintered. The sintered product is then processed through crushing, washing, sieving, and demagnetizing to obtain the cathode material matrix. The precursor has the chemical formula Ni. x Co y Mn z (OH)2, where 0≤x≤1.0, 0≤y≤1.0, 0≤z≤1.0, and x+y+z=1.
[0033] In some specific embodiments of the present invention, the sintering temperature is 600~800℃, for example, it can be any one value or a range of any two values among 600℃, 650℃, 700℃, 750℃, and 800℃; the number of sintering times is 1~3 times, for example, the number of sintering times can be 1 time, 2 times or 3 times.
[0034] In some specific embodiments of the present invention, the lithium salt used includes at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium fluoride, lithium phosphate, lithium metaborate, and lithium metaphosphate.
[0035] In some specific embodiments of the present invention, the coating source includes at least one of a compound containing M, boric acid, and phosphoric acid, wherein M is selected from at least one of Al, Zr, Mg, Ti, Li, Y, La, Co, Zn, Ce, Si, Ge, Sc, Ga, Ta, and Nb; the compound containing M includes at least one of oxides, hydroxides, alkoxides, acetates, borates, phosphates, hydrogen phosphates, dihydrogen phosphates, pyrophosphates, carbonates, and oxalates. As an example, the coating source includes one or more of aluminum acetate, cobalt acetate, yttrium acetate, lithium acetate, titanium acetate, lanthanum acetate, zirconium acetate, lanthanum hydroxide, aluminum hydroxide, lithium hydroxide, lithium dihydrogen phosphate, lithium borate, boric acid, lithium carbonate, and niobium oxalate.
[0036] In some specific embodiments of the present invention, the flux includes at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium fluoride, lithium phosphate, lithium metaborate, and lithium metaphosphate. The present invention employs a lithium-based flux-assisted melt quenching method, which can complete the coating reaction in the medium-low temperature range, avoiding prolonged high temperatures that exacerbate lithium-nickel mixing and surface structure degradation in high-nickel cathode materials. The all-lithium-based flux system does not introduce harmful impurities such as potassium and sodium, eliminating the electrical performance degradation and increased interfacial impedance caused by residual impurities at the source. Preferably, the flux is a lithium hydroxide-lithium nitrate eutectic composite system or a lithium phosphate-lithium metaborate eutectic composite system.
[0037] In some specific embodiments of the present invention, the amount of coating source added accounts for 0.1% to 5% of the mass of the cathode material matrix. For example, it can be any one value or a range of any two values from 0.1%, 0.5%, 1%, 2%, 3%, 4%, and 5%.
[0038] In some specific embodiments of the present invention, the amount of flux added accounts for 0.2% to 3% of the mass of the cathode material matrix. For example, it can be any one value or a range of any two values from 0.2%, 0.5%, 0.8%, 1%, 1.5%, 2%, to 3%.
[0039] In some specific embodiments of the present invention, in step S2, the oxygen-containing atmosphere can be an oxygen atmosphere or a mixture of oxygen and an inert gas, preferably an oxygen atmosphere.
[0040] A second aspect of the present invention provides a coated modified cathode material, prepared by any one of the preparation methods described in the foregoing embodiments; the coated modified cathode material includes a cathode material matrix and a coating layer coated on the surface of the cathode material matrix, having the general chemical formula Li. a Ni x Co y Mn z O2@Li b N c O d Where 0≤b≤7.0, 0≤c≤5.0, 0≤d≤12.0, c and d are not both 0, b, c, and d are the stoichiometric coefficients of the corresponding elements and are all non-negative rational numbers, and the compound as a whole satisfies the principle of electroneutrality; N includes one or more combinations of Al, Zr, Mg, Ti, Y, La, Co, Zn, Ce, B, P, Si, Ge, Sc, Ga, Ta, and Nb.
[0041] The modified cathode material provided by this invention can effectively improve the discharge specific capacity, first efficiency, cycle stability and thermal safety performance of lithium batteries.
[0042] In some specific embodiments of the present invention, the coating layer comprises a metal oxide and / or a lithium-based fast ion conductor.
[0043] In some specific embodiments of the present invention, the lithium-based fast ion conductor includes at least one of the following: NASICON type oxide fast ion conductor, garnet type oxide fast ion conductor, glassy composite lithium fast ion conductor, Li3PO4 fast ion conductor, LiBO2 fast ion conductor, LiAlO2 fast ion conductor, and LiNbO3 fast ion conductor.
[0044] The coating layer of this invention has both physical protection and ion conduction functions. It can stabilize the surface structure of the material, reduce the generation of microcracks during cycling, accelerate lithium-ion transport, reduce interface impedance, and simultaneously improve the specific capacity, cycle stability and thermal safety performance of the ultra-high nickel cathode.
[0045] A third aspect of the present invention provides a lithium battery comprising the coated modified cathode material described in any of the foregoing embodiments. This lithium battery exhibits high discharge specific capacity, good cycle stability, and excellent thermal safety performance.
[0046] The following detailed description of some embodiments of the present invention is provided in conjunction with specific application examples. Unless otherwise specified, all raw materials used in the embodiments can be obtained commercially available.
[0047] Example 1 (I) Preparation of cathode material matrix The precursor has the chemical formula Ni 0.90 Co 0.05 Mn 0.05 (OH)2 was mixed with lithium hydroxide at a molar ratio of 1:1.05 in a high-speed mixer until homogeneous. The mixture was then fed into a box furnace for sintering. The sintering process was first low temperature and then high temperature. The low temperature sintering heating rate was 3℃ / min, the holding temperature was 620℃, and the holding time was 6h. The high temperature sintering heating rate was 3.5℃ / min, the holding temperature was 720℃, and the holding time was 8h. The mixture was then allowed to cool naturally. The sintered product was crushed, washed, sieved, and demagnetized to obtain the ternary cathode material matrix LiNi. 0.90 Co 0.05 Mn 0.05 O2.
[0048] (ii) Coating modification S1. Weigh aluminum acetate at 1.0% of the mass of the coating source as the positive electrode material matrix, and weigh lithium hydroxide-lithium nitrate composite flux at 0.8% of the mass of the flux as the positive electrode material matrix. The molar ratio of LiOH to LiNO3 in the composite flux is 7:3, and the melting point is 230℃. Mix the positive electrode material matrix, coating source, and flux thoroughly to obtain a mixture. S2. Place the mixture in an oxygen atmosphere, first heat it to a first temperature of 400℃ for pre-melting and hold for 2 hours, then heat it to a second temperature of 720℃ for coating and holding for 3 hours.
[0049] S3. After the heat preservation is completed, the material is rapidly quenched and cooled to room temperature at a rate of 30℃ / min, and then demagnetized by sieving to obtain an ultra-high nickel cathode material uniformly coated with Al2O3 nanocrystals.
[0050] Example 2 Example 2 is similar to Example 1, except that the coating source is replaced with lithium dihydrogen phosphate, and the amount is 1.2% of the matrix mass, which finally forms a Li3PO4 fast ion conductor nanocrystalline coating layer; the first temperature is adjusted to 350°C and the second temperature is adjusted to 700°C; the remaining raw materials, process steps and parameters are the same as in Example 1.
[0051] Example 3 Example 3 is similar to Example 1, except that: the flux uses a lithium nitrate-lithium metaborate composite system with a molar ratio of 6:4, that is, the molar ratio of LiNO3 to LiBO2 is 6:4, the flux melting point is 245℃, and the amount used is 1.0% of the mass of the cathode material matrix; the second temperature is adjusted to 750℃, and the quenching cooling rate is 25℃ / min; the remaining raw materials, process steps and parameters are the same as in Example 1.
[0052] Example 4 Example 4 is similar to Example 1, except that: the coating source is a mixture of zirconium hydroxide and lithium borate, and the total amount is 1.5% of the mass of the cathode material matrix. The corresponding final coating layer is a composite nanocrystal of ZrO2 and LiBO2, and the mass ratio of the two substances in the final coating layer is about 1:1. The second temperature is adjusted to 700℃, and the other raw materials, process steps and parameters are the same as in Example 1.
[0053] Example 5 Example 5 is similar to Example 1, except that the cathode material substrate is a ternary cathode material LiNi. 0.95 Co 0.03 Mn 0.02 O2, the corresponding precursor is Ni 0.95 Co 0.03 Mn 0.02 (OH)2; the coating source was replaced with cobalt acetate, and the amount was 0.8% of the mass of the cathode material matrix, and a Co3O4 nanocrystalline coating layer was finally formed; the first temperature was 380℃, the second temperature was 680℃, the quenching cooling rate was 40℃ / min, and the remaining raw materials, process steps and parameters were the same as in Example 1.
[0054] Example 6 Example 6 is similar to Example 1, except that the cathode material substrate is a ternary cathode material LiNi. 0.5 Co 0.2 Mn 0.3 O2, the corresponding precursor is Ni 0.5 Co 0.2 Mn 0.3 (OH)2; the coating source was replaced with yttrium acetate, and the amount was 0.5% of the mass of the cathode material matrix, finally forming a Y2O3 nanocrystalline coating layer; the flux adopted was a lithium phosphate-lithium perchlorate composite system with a molar ratio of 3:2, the melting point of which was 230℃, and the amount was 0.8% of the mass of the cathode material matrix; the second temperature was 780℃, and the quenching cooling rate was 35℃ / min; the remaining raw materials, process steps and parameters were the same as in Example 1.
[0055] Example 7 Example 7 is similar to Example 1, except that the coating source is replaced with lanthanum hydroxide, and the amount used is 0.6% of the mass of the cathode material matrix, ultimately forming a La2O3 nanocrystalline coating layer; the flux is a lithium hydroxide-lithium carbonate composite system with a molar ratio of 8:2, the melting point of which is 415℃, and the amount used is 0.7% of the mass of the cathode material matrix; the first temperature is 420℃; the second temperature is 730℃; and the remaining raw materials, process steps and parameters are the same as in Example 1.
[0056] Example 8 Example 8 is similar to Example 1, except that the cathode material substrate is a ternary cathode material LiNi. 0.6 Co 0.1 Mn 0.3 O2; the coating source is a mixture of lithium dihydrogen phosphate and yttrium acetate in a mass ratio of 3:4, with a total amount of 2.0% of the cathode material matrix, ultimately forming a composite nanocrystalline coating layer of Li3PO4 and Y2O3; the flux adopts a ternary composite system of lithium hydroxide-lithium metaborate-lithium fluoride in a molar ratio of 1:1:1, with a melting point of 430℃, and an amount of 1.5% of the cathode material matrix; the first temperature is 440℃; the second temperature is 750℃, and the quenching cooling rate is 30℃ / min; the remaining raw materials, process steps and parameters are the same as in Example 1.
[0057] Example 9 Example 9 is similar to Example 1, except that: the coating source is a mixture of lithium acetate and niobium oxalate, prepared according to the stoichiometric ratio of LiNbO3; the total amount of coating source is 1.2% of the mass of the cathode material matrix, ultimately forming a LiNbO3 lithium-based fast ion conductor nanocrystalline coating layer; the first temperature is 380℃, held for 2.5h, the second temperature is 720℃, held for 4h, and the quenching cooling rate is 30℃ / min; the remaining raw materials, process steps and parameters are the same as in Example 1.
[0058] Example 10 Example 10 is similar to Example 1, except that the coating source is a mixture of lithium dihydrogen phosphate, aluminum acetate, and titanium acetate, according to Li 1.3 Al 0.3 Ti 1.7 (PO4)3 stoichiometric ratio; the total amount of coating source is 2.0% of the mass of the cathode material matrix, finally forming a NASICON type oxide fast ion conductor nanocrystalline coating layer; the flux adopts a lithium nitrate-lithium fluoride composite system with a molar ratio of 6:4, its melting point is 240℃, and the amount is 1.2% of the mass of the cathode material matrix; the first temperature is 400℃, held for 3h, the second temperature is 750℃, held for 5h, and the quenching cooling rate is 25℃ / min; the remaining raw materials, process steps and parameters are the same as in Example 1.
[0059] Example 11 Example 11 is similar to Example 1, except that the coating source is a mixture of lithium hydroxide, lanthanum acetate, and zirconium acetate, according to Li7La3Zr2O 12 The stoichiometric ratio was used for the coating; the total amount of coating source was 2.5% of the mass of the cathode material matrix, ultimately forming a garnet-type oxide fast ion conductor nanocrystalline coating layer; the flux used was a lithium hydroxide-lithium metaborate composite system with a molar ratio of 7:3, a melting point of 430℃, and an amount of 1.5% of the mass of the cathode material matrix; the first temperature was 440℃, held for 3 hours, the second temperature was 780℃, held for 5 hours, and the quenching cooling rate was 35℃ / min; the remaining raw materials, process steps, and parameters were the same as in Example 1.
[0060] Example 12 Example 12 is similar to Example 1, except that: the coating source is a mixture of lithium dihydrogen phosphate, boric acid, and lithium carbonate, measured in a molar ratio of Li2O:B2O3:P2O5 = 3:2:1; the total amount of coating source is 1.5% of the mass of the cathode material matrix, ultimately forming a Li2O-B2O3-P2O5 glassy composite lithium fast ion conductor coating layer; the flux is a lithium metaborate-lithium nitrate composite system with a molar ratio of 5:5, a melting point of 245℃, and an amount of 1.0% of the mass of the cathode material matrix; the first temperature is 360℃, held for 2 hours, the second temperature is 700℃, held for 3 hours, and the quenching cooling rate is 80℃ / min, locking the amorphous glassy structure through rapid quenching; the remaining raw materials, process steps, and conditions are the same as in Example 1.
[0061] Comparative Example 1 This comparative example is a traditional solid-phase coated modified cathode material. The difference between its preparation process and that of Example 1 is that no flux is added, and the coating source is directly mixed with the matrix; the mixture is directly sintered at 800°C in an oxygen atmosphere for 6 hours, and after sintering, it is naturally cooled with the furnace at a cooling rate of about 3°C / min; the remaining raw materials and proportions are the same as those in Example 1.
[0062] Comparative Example 2 This comparative example is similar to Example 1, except that the flux is replaced with potassium chloride (potassium salt), and the amount is the same as the flux mass in Example 1; the other raw materials, process steps and parameters are the same as in Example 1.
[0063] Comparative Example 3 This comparative example is similar to Example 1, except that in step S3, after the heat preservation is completed, the furnace is naturally cooled to room temperature at a rate of about 3°C / min; the other raw materials, process steps and parameters are the same as in Example 1.
[0064] Comparative Example 4 This comparative example is a cathode material modified by direct solid-phase coating with nanocrystals. The difference between its preparation process and that of Example 1 is that the coating source is replaced with commercial nano Al2O3 powder, and the amount is 1.0% of the mass of the cathode material matrix; no flux is added, and the mixture is directly sintered at 650°C in an oxygen atmosphere for 4 hours and then naturally cooled in the furnace; the matrix raw materials are the same as those in Example 1.
[0065] Comparative Example 5 This comparative example is similar to Example 1, except that in step S2, the temperature is directly raised to 740°C and covered for 4 hours; the other raw materials, process steps and parameters are the same as in Example 1.
[0066] Comparative Example 6 This comparative example is similar to Example 1, except that in step S2, the temperature is raised to 420°C for pre-melting and held for 6 hours, and then directly quenched and cooled to room temperature; the other raw materials, process steps and parameters are the same as in Example 1.
[0067] Test case Lithium secondary batteries were prepared using the coated modified cathode materials prepared in each embodiment and each comparative example, and their electrochemical performance was tested.
[0068] Lithium-ion battery manufacturing: The modified positive electrode material, carbon nanotubes, conductive carbon black, and binder polyvinylidene fluoride were dispersed in N-methyl-2-pyrrolidone solvent at a weight ratio of 96.9:0.3:1.0:1.8 and mixed evenly to prepare a positive electrode slurry. Then, the positive electrode slurry was coated onto aluminum foil, and after drying, rolling, and slitting, a positive electrode sheet was obtained. The positive electrode, separator, lithium sheet, etc. are assembled into a coin cell in sequence and left to stand for 24 hours for electrochemical testing.
[0069] Chemical performance testing: The coin cells, after being left to stand as described above, were charged at 20°C with a constant current of 0.1C to 4.35V, and then discharged at a constant current of 0.1C to 2.80V to measure the initial discharge capacity and coulombic efficiency. Subsequently, each secondary cell after the initial charge / discharge was charged at 45°C with a constant current of 0.50C to 4.3V, and then discharged at a constant current of 1.0C to 2.80V, constituting one cycle. Fifty charge / discharge cycles were then performed to measure capacity retention.
[0070] DSC test: After charging the assembled lithium-ion battery to 4.35V (0.1C), the electrode was removed from the coin cell, cleaned with DMC, dried at 60℃ for 30min, and then DSC test was performed. Temperature range: 0~400℃, heating rate: 10℃ / min.
[0071] The test results are shown in Table 1.
[0072] Table 1
[0073] As shown in Table 1, all samples in the examples exhibited excellent electrochemical performance and thermal stability. Comparative Examples 1 and 4, using a conventional dry coating process, showed a significant decrease in discharge capacity compared to the examples; simultaneously, due to insufficient uniformity in the dry coating, the cycle performance degradation was exacerbated, and thermal stability also decreased. Comparative Example 2, due to the introduction of potassium impurities into the system, experienced a significant deterioration in discharge capacity, and its cycle performance and thermal stability also showed significant disadvantages. Comparative Examples 3, 5, and 6 removed the quenching process, the first pre-melting temperature zone, and the second high-temperature coating temperature zone, respectively. Test results showed that the absence of any of these key process steps resulted in capacity degradation, a significant decrease in cycle performance, and a significant decline in thermal stability.
[0074] Although the present invention has been illustrated and described with specific embodiments, it should be understood that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; those skilled in the art should understand that modifications can be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features therein, without departing from the spirit and scope of the present invention; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention; therefore, this means that all such substitutions and modifications that fall within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a coated modified cathode material, characterized in that, Includes the following steps: S1. The positive electrode material matrix is mixed with the coating source and flux to obtain a mixture; S2. The mixture is subjected to segmented heat treatment in an oxygen-containing atmosphere, the segmented heat treatment comprising: heating the mixture to a first temperature and holding it at that temperature, then continuing to heat it to a second temperature and holding it at that temperature, wherein the first temperature is higher than the melting point of the flux, and the second temperature is greater than the first temperature; S3. After the segmented heat treatment is completed, cooling is performed at a rate of ≥20℃ / min.
2. The method for preparing the coated and modified cathode material according to claim 1, characterized in that, The first temperature is 300~500℃, and the holding time at the first temperature is 1~4h.
3. The method for preparing the coated and modified cathode material according to claim 1, characterized in that, The second temperature is 650~850℃, and the holding time at the second temperature is 2~6h.
4. The method for preparing the coated and modified cathode material according to claim 1, characterized in that, The chemical formula of the cathode material matrix is Li. a Ni x Co y Mn z In the chemical formula O2, 0.97≤a≤1.10, 0≤x≤1.0, 0≤y≤1.0, 0≤z≤1.0, and x+y+z=1.
5. The method for preparing the coated and modified cathode material according to claim 1, characterized in that, The coating source includes at least one of a compound containing M, boric acid, and phosphoric acid, wherein M is selected from at least one of Al, Zr, Mg, Ti, Li, Y, La, Co, Zn, Ce, Si, Ge, Sc, Ga, Ta, and Nb; the compound containing M includes at least one of oxides, hydroxides, alkoxides, acetates, borates, phosphates, hydrogen phosphates, dihydrogen phosphates, pyrophosphates, carbonates, and oxalates containing M.
6. The method for preparing the coated and modified cathode material according to claim 1, characterized in that, The flux includes at least one of lithium hydroxide, lithium nitrate, lithium carbonate, lithium fluoride, lithium phosphate, lithium metaborate, and lithium metaphosphate.
7. The method for preparing the coated and modified cathode material according to claim 1, characterized in that, It meets at least one of the following characteristics: (1) The amount of the coating source added accounts for 0.1% to 5% of the mass of the cathode material matrix; (2) The amount of flux added accounts for 0.2% to 3% of the mass of the cathode material matrix.
8. A coated and modified cathode material, characterized in that, The modified cathode material is prepared by any one of claims 1 to 7; the modified cathode material includes a cathode material matrix and a coating layer covering the surface of the cathode material matrix.
9. The coated and modified cathode material according to claim 8, characterized in that, The coating layer comprises a metal oxide and / or a lithium-based fast ion conductor; Preferably, the lithium-based fast ion conductor includes at least one of the following: NASICON type oxide fast ion conductor, garnet type oxide fast ion conductor, glassy composite lithium fast ion conductor, Li3PO4 fast ion conductor, LiBO2 fast ion conductor, LiAlO2 fast ion conductor, and LiNbO3 fast ion conductor.
10. A lithium battery, characterized in that, Including the coated modified cathode material as described in claim 8 or 9.